Influence of the Cobalt Additive on the Flux Cored Wire of System Fe-C-Si-Mn-Cr-Ni-Mo-V; Key Engineering Materials; Vol. 736 : Materials and their Application - Osetkovskiy I. V.; Kozyrev N. A.; Gusev A. I.; Kozyreva O. A.; Gizatulin R. A. Rinat Akramovich; Valueva A. V. Anna Vladimirovna (2017, 2017)
Title screen